Estimation of some Essential oils and study Antibacterial activity of Rosmarinus officinalis Extract - Hossain, Madeha; Al-khazraji, Shahbaa M.; Hassoon, Ali (Journal of Biomedicine and Biochemistry, 2022)
The study was done to look into the antibacterial activity of equeous and methalonic extracts of the Rosmarinus officinalis leaves on the growth repression of Staphylococcus aureus and Escherichia coli in vitro. The disc diffusion method was employed to determine the sus- ceptibility of the bacteria tested to the two rosemary extracts. In order to compare the activity of two extracts, gentamicin (300 mg/ml) was used as a positive control. The results demonstrated that the two ex- tracts exhibit antibacterial efficacy in inhibiting the development of tested microorganisms. In examined bacteria, the methalonic extract inhibited growth more than the equeous extract, and S. aureus was more susceptible to the action of the two extracts than E. coli. Some of the medically important oils in rosemary have been estimated (Ci- neole, Camphor, Linalool)%. The results showed that the alcoholic extract gave higher results than the aqueous extract